Journal of Political Economy (Journal of Political Economy, 2017)
Next article FreeJournal of Political EconomyPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Daron AcemogluDaniel AckerbergSumit AgarwalAnna AizerUfuk AkcigitTreb AllenDouglas AlmondItai AshlagiEnghin AtalayDavid AtkinYu AwayaEduardo AzevedoPierre AzoulayManuel BaguesMiguel BallesterChristiane BaumeisterChristian BelzilDaniel BenjaminMark BilsLarry BlumeJaroslav BorovickaJohn BoundLeah BoustanChad BownBart BronnenbergBen BrooksEric BudishKonrad BurchardiDavid BurkMarshall BurkeColin CamererAndrew CaplinPedro CarneiroKatherine CaseyDeborah Cobb-ClarkTimothy CogleyOlivier CoibionShawn ColeGeorge ConstantinidesAdam CopelandThomas CovertSteven DavisJan De LoeckerMarco Del NegroMelissa DellMarco di MaggioRafael Di TellaJonathan DingelWill DobbieMark EganJason FabermanIvan Fernandez-ValChristian Fons-RosenAndrew FosterChao FuTitus GalamaDouglas GaleGerd GigerenzerUri GneezyLimor GolanYuriy GorodnichenkoDavid GreenDonald GreenMatthew GrennanJeff GroggerLuigi GuisoRong HaiYoram HalevyJames HamiltonJoseph HarringtonGlenn HarrisonMarc HenryKyle HerkenhoffJonas HjortElisabeth HonkaJohn Eric HumphriesYannis IoannidesNir JaimovichPrzemyslaw JeziorskiDavid JohnsonCharles JonesJoonhwi JooAlejandro JustinianoArturs KalninsLouis KaplowLoukas KarabarbounisTim KautzBen KeysPatrick KlineFuhito KojimaHideo KonishiWojciech KopczukMatthew KotchenNicolai KuminoffChristoph KuzmicsThibaut LamadonHoracio LarreguyLungFei LeePatrick LegrosThomas LemieuxRasmus LentzJacob LeshnoDanielle LiC.-Y. Cynthia Lin LawellMikael LindahlJohn ListLance LochnerAprajit MahajanGregor MatvosTimothy McQuadeNeil MehrotraStephan MeierGuido MenzioPascal MichaillatStelios MichalopoulosPedro MiraAnirban MitraAhmed MobarakEmanuel MoenchFrancesca MolinariAndreas MoxnesKathleen MullenTakeshi MurookaRoger MyersonPaulo NatenzonDerek NealChris NoskoMatthew NotowidigdoPhilip OreopoulosMatthew OsborneAmanda PallaisElias PapaioannouRonni PavanKaren PenceJohn PepperWolfgang PesendorferJorn-Steffen PischkeTomasz PiskorskiRobert PollakMaria PolyakovaDavid PorterMichael PowellVictoria ProwseBenjamin PugsleyNancy QianAnita RaoSergio RebeloRichard RobbArthur RobsonAdam RosenMark RosenzweigHeather RoyerAldo RustichiniBernard SalanieJames SalleeBen SandEmily SandsYuliy SannikovPaola SapienzaRichard SchmalenseeLawrence SchmidtMartin SchneiderAndrew ScottAmit SeruAnanth SeshadriRobert ShimerKelly ShuePaolo SiconolfiHolger SiegRui SilvaMichael SinkinsonGary SolonPaulo SomainiPeter SorensenStefanie StantchevaMelvin StephensJoerg StoyePer StrombergAmir SufiTakuo SugayaTavneet SuriJakob SvenssonBalazs SzentesChristopher TaberScott TaylorPetra ThiemannRebecca L. ThorntonSergio UrzuaRobert VallettaEllen VerbakelFrank VerbovenRobert VishnyXavier VivesPeter WakkerChristopher WaltersDavid WeilNoam YuchtmanJunsen ZhangOwen ZidarEric Zitzewitz Next article DetailsFiguresReferencesCited by Journal of Political Economy Volume 125, Number 1February 2017 Article DOIhttps://doi.org/10.1086/691151 © 2017 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.